Candida antarctica B Lipase-Loaded Microreactor for the Automated Derivatization of Lipids. (13th June 2017) - Mugo, Samuel M.; Tiedemann, Kyle
ABSTRACT: A key bottleneck in the profiling of lipids is the multistep derivatization required prior to gas chromatography (GC) analysis. A single in-vial lipid derivatization and analysis may significantly minimize sample loss and improve analytical sensitivity. A cotton fiber-supported poly(glycidylmethacrylate- co -ethylene glycol dimethacrylate) polymer microbrush microreactor loaded with Candida antarctica lipase B was developed for the facile conversion of triacylglycerols into fatty acid ethyl ester derivatives for gas chromatograph–mass spectrometry (GC–MS) analysis. The polymer microbrush microreactor was fabricated in effort to provide efficient, simplified, cost effective, and high-throughput GC–MS determination of triacylglycerols. The polymer microbrush microreactor was used as an in-vial triacylglycerol transesterification platform, with economical sample consumption of less than or equal to 100 µL and significant reduction of reagents. To evaluate the polymer microbrush microreactor performance for lipids, a triolein standard and camelina oil triacylglycerols were quantitatively transformed into ethyl oleate and fatty acid ethyl esters, respectively, following a 3 h reaction time. The lipase-loaded cotton fiber-supported poly(glycidylmethacrylate- co -ethylene glycol dimethacrylate) polymer microbrush microreactors were reusable for up to five times for quantitative transesterification with minimal loss of lipase activity.